INFLUENCE OF FINANCIAL REPORT QUALITY, AUDIT QUALITY, AND ENVIRONMENTAL, SOCIAL, AND GOVERNANCE ON INVESTMENT EFFICIENCY - Chandra, Jesica Amalia; Handoko, Jesica; Mokoginta, Dirgantara Dahana (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Research was conducted to identify and analyze the impact of financial report quality, audit quality, and Environmental, Social, and Governance (ESG) on investment efficiency with company size, leverage, and industry type as control variables. The data in this research are quantitative data obtained secondarily from the annual reports of non-financial companies listed on the IDX for the 2020-2022 period and ESG scores published by Bloomberg Terminal. The data were analyzed with multiple linear regression models and processed using SPSS software version 23. The findings of this research are that financial report quality and audit quality have a significant and positive impact on investment efficiency, while ESG has no impact on investment efficiency. These findings are expected to provide additional knowledge and empirical evidence related to factors that have an impact on investment efficiency and provide knowledge for companies and investors in order to make the right decisions regarding efficient investment. This research has limitations, namely using ESG scores from Bloomberg where the data obtained is the final result so that the value of its various aspects, namely environmental, social, and governance, is unknown. This means that it is not known specifically what aspects of the company are good. This research does not classify investment efficiency into overinvestment, underinvestment, and efficient conditions.